THE ESSENCE OF THE CATEGORY ‘CONSUMER CREDIT’ - Oleg E. Gordienov (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
The article investigates the wording of the category ‘credit’. It enumerates key features of the credit. On the basis of distinguishing characteristics the field of consumer credit was identified. The broad interpretation of consumer credit was provided with classifications by certain criteria. The article shows the difference between mortgage credit and consumer credit and formulates narrower, western interpretation of consumer credit. The author discusses different views on the essence of the category ‘consumer credit’ – POS – credits and non-target bank credits, as well as other limits of understanding. The author formulated his own idea of consumer credit by incorporating retail and mortgage crediting in this notion. As a result the author gives the definition of the category ‘consumer credit’.